Impact Analysis Of Partnership Between Small Retailers And The Sampoerna Retail Community Distribution Company In Sukoharjo Regency - Kurniawan, Aditya Wahyu; Susilo, Agus (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to analyze the impact of a strategic partnership between small retailers (MSMEs) and the Sampoerna Retail Community (SRC) distribution company in Sukoharjo Regency. This partnership serves as a strategy for empowering MSMEs through coaching, mentoring, and digitalization of store operations. The study used a descriptive qualitative approach with data collection techniques through in-depth interviews, observation, and documentation of three SRC partner grocery store owners. The results show that the partnership has a positive impact on store modernization, operational efficiency through the "AYO TOKO" digital application, increased sales, and consumer loyalty. However, this partnership also poses challenges such as demands for standard adjustments and dependence on the SRC distribution system. These findings reinforce the theory of strategic partnerships, where collaboration between entities can create mutual competitive advantages. This study recommends the importance of strengthening the adaptive capacity of small retailers and the need for two-way participation in the formulation of partnership policies to ensure sustainability and fairness in business relationships.